.NET 2.0 for Delphi Programmers - Shemitz, Jon (Apress, 2012)
It’s rough being a Delphi programmer. We know we have a wonderful, productive environment— but jobs are few and far between. We know that we can write any sort of application with Delphi—yet Delphi is seen as a GUI builder and a database front-end. We’ve all seen (or at least heard of) systems where the ‘interesting parts’ are written in C or C++, in DLLs, and Delphi is just used for the GUI interface. We may know C++ and have significant Win32 experience—and yet not been considered for C++ jobs because we didn’t know MFC or ATL. .NET changes that. All .NET languages use the same Framework Class Library (FCL). Learn the FCL—in any language—and you’re a .NET programmer. “Learn once, work anywhere.” What split the Windows programming world into mutually incompatible Delphi shops, VB shops, and C++ shops was never the languages themselves. Picking up any particular language has always been easy. The barriers to entry have always been the different libraries. Using a different language meant learning a new library. Learning a new library meant that every little thing required a documentation search; your productivity was near zero for weeks on end. But with .NET, once you learn the Framework Classes, you can easily move from project to project and from job to job.